Advanced metameric dimension framework for heterogeneous industrial Internet of things. (13th July 2020) - Khan, Mohammad Ayoub; Abuhasel, Khaled Ali
Abstract: The heterogeneous industrial Internet of things (HetIoT) is a recent area of research that can change both our perception of fundamental informatics and the effectiveness of future machines. The HetIoT is rapidly used in a variety of industries, including healthcare smart cities, smart mobility, smart transportation, and advanced manufacturing. In industrial settings, outdated machines consume an inordinate amount of energy and time to produce effective output. The efficient functioning of the HetIoT machines plays a vital role in the industrial management. To demonstrate efficiency of the functioning, the continuous monitoring of machines becomes mandatory. To describe the efficiency of updated HetIoT machines, this article introduces the concept of advanced machine‐metameric dimension (A m D) to analyze efficacy, efficiency, and effectiveness. This article proposes a HetIoT framework to identify the real‐time resembling of continuous monitoring of a metameric dimension of the machines. This demonstration of the concept is attempted through the analysis of machine efficiency, efficacy, effectiveness, and so on. The proposed A m D with a HetIoT has achieved higher precision, recall, F1‐Score, and higher purity.